Molecular Recognition, Transient Chirality and Sulfur Hydrogen Bonding in the Benzyl Mercaptan Dimer - Rizalina Tama Saragi (MDPI AG, 2021)
The homodimers of transiently chiral molecules offer physical insight into the process of molecular recognition, the preference for homo or heterochiral aggregation and the nature of the non-covalent interactions stabilizing the adducts. We report the observation of the benzyl mercaptan dimer in the isolation conditions of a supersonic jet expansion, using broadband (chirped-pulse) microwave spectroscopy. A single homochiral isomer was observed for the dimer, stabilized by a cooperative sequence of S-H···S and S-H···π hydrogen bonds. The structural data, stabilization energies and energy decomposition describe these non-covalent interactions as weak and dispersion-controlled. A comparison is also provided with the benzyl alcohol dimer.